(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
The purpose of this study was to determine the Quality of Service for Making Land Purchase Deed in the District of Pineleng, Minahasa Regency. This research uses qualitative research methods. There are 8 informants in this study consisting of sub-district heads (1 person), sub-district secretaries (1 person), subdistrict staff who handle AJB (1 person), and the community (5 people). Based on the results of research that has been done by the author, In general the Service Quality of Making Land Purchase Deed can be seen from 3 (three) dimensions of service quality, namely: (1) Reliability (reliability) here the reliability of employees in providing services that are fast, precise, easy and smoothly becomes an evaluation condition for the people being served. In terms of speed, the accuracy of employees in the Pineleng District Office when making arrangements or services can be said to be quite good. However, there are still people who, when making arrangements, still lack understanding of the completeness of the file, which is the obstacle here, namely the lack of providing information about AJB management procedures to the public. (2) Responsiveness (responsiveness), the service procedure for making Land Purchase Deed in Pineleng District in this case regarding the responsiveness of its employees when performing services to the community can be said to be good and for the level of absorption, the understanding of all complaints and understandings to the community is also quite good . (3) Empathy (empathy), shows the ability to understand the people who are served with attention, seriousness, sympathetic, and understanding. According to all the informants’ answers, the empathy attitude from the employees was good enough, but there were still people who could not complete the management process. The problem is the lack of employee openness to the community. And also still found special treatment to other communities. Keywords: Quality, Service, Land Purchase Deed